Mortality, Morbidity, and Costs After Implementation of a Vasopressin Guideline in Medical Intensive Care Patients With Septic Shock: An Interrupted Time Series Analysis. Issue 4 (April 2020) - Bauer, Seth R.; Sacha, Gretchen L.; Reddy, Anita J.
Background: Vasopressin decreases vasopressor requirements in patients with septic shock. However, the optimal norepinephrine dose for initiation or cessation of vasopressin is unclear.Objective: Analyze monthly intensive care unit (ICU) mortality rates 1 year preimplementation and postimplementation of a guideline suggesting a norepinephrine dose of 50 µg/min or more for initiation of vasopressin and early cessation of vasopressin.Methods: This retrospective quasi-experimental study included adult patients with septic shock admitted to the medical ICU of a tertiary care medical center over 2 years. Time periods were evaluated with interrupted time series analysis.Results: A total of 1148 patients were included: 573 patients preguideline and 575 patients postguideline. Group characteristics were well balanced at baseline, except patients postguideline had higher sequential organ failure assessment scores. Postguideline, fewer patients were initiated on vasopressin (305 [53.2%] vs 217 [37.7%], absolute difference −15.5% [95% CI −21.2% to −9.8%]), and the norepinephrine dose at vasopressin initiation was higher (median 25 [interquartile range 18, 40] µg/min vs 40 [22, 52] µg/min; median difference 15 [95% CI 11 to 19] µg/min; P < 0.01). After guideline implementation, there was no evidence for a difference in ICU mortality rate slope (slope change 0.07% [95% CI −0.8% to 1.0%] per month; P 0.87), but the vasoactive cost level decreased by US183 (95% CI −US327 to −US39) per patient immediately after implementation.Conclusion and Relevance: Implementation of a guideline suggesting a high norepinephrine dose threshold for vasopressin initiation and early vasopressin cessation in patients with septic shock appears to be safe and may decrease vasoactive costs.